Experimental study on service performance of epoxy asphalt steel deck pavement of cable stayed bridge. (December 2020) - Zhang, Hui; Mao, Quan; Zhu, Zhiyuan; Zhang, Zhixiang; Pan, Youqiang; Wan, Jianjun; Zhou, Chengqi; Qian, Jie
Abstract: After a cable-stayed bridge was opened to traffic in 2008, as of October 2017, various types of diseases have appeared in epoxy asphalt concrete pavement. However, as of now, the durability evaluation of steel bridge deck pavement is almost blank during the operation period. Therefore, the research team investigated and tested the service performance of epoxy asphalt concrete pavement on the cable-stayed bridge. The results showed that the intensity has attenuated to varying degrees at different positions of the heavy lane, and the most damaged area was the pavement of the uphill section. The crack resistance of the epoxy asphalt mixture was less affected by external conditions. In the composite beam, the bending strength of the mixture was significantly decreased where was under complex stress and threat of disease, and the deformation performance increased initially and then decreased. There was a bridge pavement that was under delamination and complex stress in the single layer beam, the low temperature performance of the lower layer of the pavement was inferior to that of the upper layer of the pavement. The epoxy asphalt mixture had good water stability. The fatigue life of epoxy asphalt mixture was more sensitive to the change of strain, and the change of modulus showed a gradual decay trend. It has been unable to meet the working environment under large strain conditions.